Peran Lembaga Swadaya Masyarakat dalam Jejaring Kebijakan Publik di Kabupaten Garut - Rizky Ilhami (Pusat Riset dan Inovasi Nasional, 2025)
Non-governmental organizations (NGOs) play an important role in public policy networks as representatives of community interests, government partners, and advocacy actors. This study aims to analyze the role of NGOs in public policy networks in Garut Regency, as well as the challenges faced in increasing their contribution to policy formulation and implementation. The study uses a qualitative approach with descriptive-analytical methods. Data were collected through in-depth interviews, observations, and documentation studies of actors involved in the policy network. The results show that NGO involvement is still symbolic, power relations between actors are not yet equal, NGO institutional capacity is limited, and coordination within the policy network is less than optimal. The lack of regulatory support also weakens the position of NGOs in the public policy process. This study concludes that strengthening the role of NGOs through institutionalizing their involvement, developing regulations, increasing capacity, and establishing equal partnership patterns are important steps to improve the effectiveness of public policy networks in Garut Regency.